Regulating effect of dietary antioxidant quality on association between estimated glucose disposal rate and moderate to severe periodontitis - Wang, Ge; Zhang, Yujie; Li, Fengli (Frontiers in Nutrition, 2025)
AimTo investigate the associations of the estimated glucose disposal rate (eGDR) and the Dietary Antioxidant Quality Score (DAQS) with periodontitis, and assessed the potential regulating effect of DAQS on relationship between eGDR and periodontitis, to provide some references for management and control of periodontitis.MethodsData of 9,588 individuals were extracted from the National Health and Nutrition Examination Survey (NHANES) database in 2009–2014 in this cross-sectional study. Associations of eGDR and DAQS with periodontitis were evaluated by multivariate logistic regression analysis, with odds ratio (OR) and 95% confidence interval (CI). The potential regulating effect of DAQS on association between eGDR and periodontitis was investigated using multiplicative interaction term, and analyzed in subgroups of age, gender, overweight and diabetes mellitus (DM). Additionally, the value of eGDR on periodontitis identification was compared with common insulin resistance (IR)-related indexes via the receiver operating characteristic (ROC) curve with area under the curve (AUC) and Delong test.ResultsAmong eligible participants, 3,111 had periodontitis stage I/II, and 6,477 had periodontitis stage III/IV. After adjusting for the selected covariates, an eGDR of <8.296 was associated with increased odds of moderate to severe periodontitis (OR = 1.28, 95%CI: 1.07–1.53), comparing to that of ≥8.296. An eGDR level of <8.296 was positively associated with increased odds of periodontitis, when individuals with a DAQS of <3 (OR = 1.67, 95%CI: 1.13–2.48), and however, this relationship was not significant among participants with DAQS of ≥3 (p = 0.051). The significant multiplicative interaction terms of eGDR and DAQS were observed in age ≥60 years (OR = 3.86, 95%CI: 1.95–7.62), female (OR = 1.68, 95%CI: 1.14–2.45), BMI ≥ 25 kg/m2 (OR = 1.53, 95%CI: 1.01–2.33), and non-DM (OR = 1.52, 95%CI: 1.06–2.18) subgroups. Furthermore, the ROC curve showed that eGDR has a relatively good value on periodontitis identification comparing to other IR-related indexes, with an AUC (95%CI) of 0.603 (0.585–0.620), and Delong test p-values of <0.001.ConclusionA higher DAQS had a potential antagonistic effect on increased moderate to severe periodontitis risk associated with lower eGDR level. Clinicians could focus on eGDR level that may identify the potential risk of periodontitis, and improving DAQS levels may help the prevention and intervening measure in periodontitis.